Investigation of Cytotoxic, Antioxidant, Apoptotic/Necrotic Activity of Aquilaria agallocha Root Extract and Determination of Gene Expression Levels in HepG2, MCF-7 Cancer Cell Lines - Dalkilic, Semih; Dalkilic, Lutfiye Kadioglu; Isbenov, Elgun; Uygur, Lutfu; Tasdemir, Ceydanur (Mdpi, 2025)
Cancer is a common disease worldwide, and medicinal plants are widely used for its treatment. A. agallocha is a plant from the Thymelaeaceae family that is endemic to East Asia. Popularly known as the agar tree, this plant is used in the treatment of heart diseases, asthma, cough, ulcers, gout, inflammation, and pain. In this study, the cytotoxic, apoptotic/necrotic, and antioxidant activities of root extracts of A. agallocha and their effects on gene expression were investigated. Cytotoxic effects were analyzed by the MTT assay method, apoptotic/necrotic effects by the double staining method, and antioxidant effects by the DPPH radical scavenging assay. According to the results, the best cytotoxic effect in HepG2 cells was observed at 1000 mu g/mL hexane extract. In MCF-7 cells, 250 mu g/mL hexane extract showed the best activity. Antioxidant activity was highest in dH2O and lowest in the methanol extract. In gene expression analysis, hexane and methanol extracts decreased p53 expression in HepG2 cells, while acetone extract increased it. In addition, the expression of Bax and Bcl-2 genes generally increased. This study revealed the potent cytotoxic, antioxidant, and apoptotic effects of the A. agallocha extract.
Keywords: cytotoxic activity; antioxidant activity; apoptosis; necrosis; expression level